Implementing Health Safety Environment (HSE) Process Management to Improve HSE Performance, Competitive Advantage and Financial Performance - Purwanto, Agustinus Hariadi DJoko; Suharjo, Budi; Sumarwan, Ujang; Daryanto, Heny K (Jurnal Manajemen Teknologi, 2014)
Abstract. Performance of health safety environmental (HSE) has been tightly demanded by stakeholders (customer, government, public, NGO, employee) and become essential factors of organization’s competitive advantages. High HSE performance leads to improving customer satisfaction, legitimacy and reputation from which better financial performance can be gained. In order to do that, companies must implemement HSE process management. The research aims to investigate effects of the four constructs, namely process management, HSE performance, organization’s competitive advantage and financial performance. The study uses descriptive and quantitative statistical methods involving 119 companies of which SEM is used to see linkages between factors. The testing results show that the process management gives significant positive effect to HSE performance after which it simulataneously affect significant and positively to competitive advantage but it has no significant relationship with financial performance. However, competitive advantage affect positively to financial performance. In conclusion, HSE process management improves HSE performance, which subsequently increases Competitive advantage but it does not affect financial performance. The increase of financial performance is given by competitive advantage.Key words: HSE, Performance, Competitive Advantages, Financial Performance, SEM Abstrak. Kinerja lingkungan dan keselamatan dan kesehatan kerja (LK3) telah dituntut dengan ketat oleh para pemangku kepentingan (pelanggan, pemerintah, masyarakat, LSM, karyawan) dan menjadi faktor-faktor esensial bagi keunggulan kompetitif organisasi. Untuk itu, perusahaan harus menerapkan manajemen proses LK3. Kinerja LK3 tinggi memberikan kepuasan pelanggan, legitimasi dan reputasi sehingga kinerja finansial dapat diperoleh. Penelitian ini bertujuan untuk mengamati pengaruh-pengaruh empat konstruk, yaitu Manajemen proses LK3, Kinerja LK3, Keunggulan kompetitif dan Kinerja finansial. Penelitian menggunakan metode analisa deskriptif dan kuantitatif yang meliputi 119 perusahaan dimana SEM diterapkan untuk melihat hubungan-hubungan antar faktor secara simultan. Hasil penelitian menunjukkan bahwa Manajemen proses LK3 memberikan pengaruh positif terhadap Kinerja LK3 yang selanjutnya secara simultan memberikan pengaruh positif terhadap Keunggulan kompetitif dan tidak memiliki pengaruh signifikan terhadap Kinerja finansial. Tetapi, Keunggulan kompetitif memberikan pengaruh positif terhadap Kinerja financial. Kesimpulan yang diambil adalah penerapan manajemen proses LK3 meningkatkan Kinerja LK3 yang selanjutnya meningkatkan Keunggulan kompetitif tetapi tidak mempengaruhi Kinerja finansial. Peningkatan kinerja finansial diberikan oleh keunggulan kompetitif.Kata kunci: LK3, Kinerja, Keunggulan Kompetitif, Kinerja Finansial, SEM